HaCaT 인간 각질세포에서 산화적 스트레스에 대한 머루근 수용성 추출물의 세포 보호 효과 - 최은옥(Eun Ok Choi); 권다혜(Da Hye Kwon); 황보현(Hyun Hwang-Bo); 정진우(Jin-Woo Jeong); 남원석(Won Sok Nam); 이연희(Youn Hee Lee); 양혜경(Hye Kyung Yang); 황혜진(Hye Jin Hwang); 김병우(Byung Woo Kim); 이승훈(Seung Hun Lee); 최영현(Yung Hyun Choi) (Han'guk Sikp'um Yŏngyang Kwahakhoe chi, 2018)
왕머루(Vitis amurensis Rupr.)의 뿌리(머루근)는 한국을 비롯한 아시아 각국에서 다양한 질환의 예방과 치료의 목적으로 오랫동안 사용되어 왔다. 비록 머루근 추출물의 항산화 효과에 대한 몇몇 보고가 있었지만, 근본적인 분자생물학적 기전 연구는 아직 완전히 이해되지 못하고 있다. 본 연구에서는 HaCaT 각질세포에서 산화적 스트레스(H2O2)에 대한 머루근 열수 추출물(WEVA)의 세포 보호 효과를 조사하였다. 본 연구의 결과에 의하면 WEVA는 H2O2에 의한 HaCaT 각질세포의 생존력 저하를 현저하게 억제시켜 WEVA가 산화적 스트레스에 대한 보호 효과가 있음을 보여주었다. WEVA는 또한 H2O2에 의한 PARP 분해와 pro-caspase-9와 -3의 발현 억제를 차단함으로써 H2O2에 의한 apoptosis를 효과적으로 억제시켰다. 이러한 WEVA의 apoptosis 억제 효과는 H2O2에 자극받은 HaCaT 세포에서 미토콘드리아 기능 손상의 감소 및 pro-apoptotic Bax와 anti-apoptotic Bcl- 2의 발현 변화의 차단과 관련이 있었다. 또한, WEVA는 H2O2에 의해 유도된 세포 내 ROS 축적과 DNA 손상을 억제하였고, Nrf2의 발현 증가와 관련된 강력한 항산화 효소인 HO-1과 NQO-1의 발현을 유도하였다. 이러한 결과는 WEVA가 ROS의 생성 억제 및 Nrf2 신호 전달계 활성을 통하여 각질세포를 산화적 스트레스에 의한 apoptosis 및 DNA 손상으로부터 보호하였음을 의미한다. 따라서 본 연구의 결과는 WEVA가 산화적 스트레스로 인한 피부질환의 치료 및 예방을 위한 기능성 소재로 유용성이 있음을 보여주었다. Root of Vitis amurensis Rupr., a wild-growing grape species, has been used as a traditional medicine for the treatment of various diseases in Asian countries, including Korea. Although several studies on the antioxidant effects of V. amurensis root extracts have been carried out, the underlying molecular mechanisms remain largely unresolved. In the present study, we investigated the cytoprotective efficacies of water extract of V. amurensis root (WEVA) against oxidative stress (hydrogen peroxide, H2O2) in HaCaT human keratinocytes. Our data show that treatment with WEVA prior to H2O2 exposure significantly increased HaCaT cell viability, indicating that exposure of HaCaT cells to WEVA conferred a protective effect against oxidative stress. WEVA preconditioning also effectively inhibited H2O2-induced apoptotic cell death by blocking degradation of poly (ADP-ribose) polymerase and down-regulation of pro-caspases-9 and -3. The anti-apoptotic effects of WEVA were associated with attenuation of mitochondrial dysfunction and normalization of expression changes of pro-apoptotic Bax and anti-apoptotic Bcl-2 in H2O2-stimulated HaCaT cells. In addition, WEVA abrogated H2O2-induced intracellular reactive oxygen species (ROS) accumulation and phosphorylation of histone H2AX at serine 139, a widely used marker of DNA damage. Moreover, WEVA increased the levels of hemeoxygenase-1 and NAD(P)H-quinone oxidoreductase-1, potent antioxidant enzymes associated with induction of nuclear transcription factor erythroid-2-like factor 2 (Nrf2). Thus, the present study demonstrates that WEVA protects human keratinocytes against oxidative stress-induced apoptosis and DNA damage, possibly through prevention of ROS generation and activation of Nrf2 signaling. Our data indicate that WEVA may potentially serve as an agent for treatment and prevention of skin disorders caused by oxidative stress. KCI Citation Count: 0